Technology-Enhanced Paraphrasing Tool to Improve EFL Students’ Writing Achievement and Enjoyment - Ariyanti, Ariyanti; Anam, Syafi'ul (Yayasan Visi Intan Permata, 2021)
The issue of plagiarism and EFL students’ difficulties in writing course appeared to be still the challenging task for teachers. Various efforts in order to increase students’ competence in producing a decent writing production are still fascinating until the present time. Therefore, the aim of this research is to examine whether the use of Technology-Enhance Paraphrasing Tool (TEPT) can improve EFL students’ writing performance. Additionally, the way the students react emotionally towards the use of TEPT in writing class, especially in paraphrasing activities was also measured to by the use of Foreign Language Enjoyment (FLE) questionnaire. Paired sample t-test was employed to 48 students from English Department at one of Private Universities in Samarinda, East Kalimantan, Indonesia. The findings showed that there was a significant effect towards the use of TEPT in writing class to improve EFL students writing achievement. In addition, all of the students performed positive emotions during the implementations of TEPT in writing class where the results from FLE questionnaire indicated that the students enjoy and being motivated in joining the writing class. Pedagogical implication of the research also discussed further in this article.